A new species of Erythroxylum (Erythoxylaceae) from the seasonal dry forests of the state of Goiás, Brazil - Silva, Marcos José Da; Loiola, Maria Iracema Bezerra (Phytotaxa, 2021)
Erythroxylum niquelandense is here described, illustrated and compared morphologically with similar congeners. Additionally, its taxonomic position, flowering and fruiting periods, geographical distribution, and conservation assessment are presented, as well as representative images and a distribution map.